Experimental and natural infections of white-tailed sea eagles (Haliaeetus albicilla) with high pathogenicity avian influenza virus of H5 subtype - Fujimoto, Yoshikazu; Ogasawara, Kohei; Isoda, Norikazu; Hatai, Hitoshi; Okuya, Kosuke; Watanabe, Yukiko; Takada, Ayato; Sakoda, Yoshihiro; Saito, Keisuke; Ozawa, Makoto (Frontiers in Microbiology, 2022)
White-tailed sea eagle (Haliaeetus albicilla), a regionally rare species of raptor, is threatened in several countries. To assess the risk of H5 high pathogenicity avian influenza (HPAI) viral infection in rare bird species, we performed experimental infections with a GS/GD96-lineage H5N6 HPAI virus of clade 2.3.4.4e in white-tailed sea eagles. Additionally, during the winter of 2020–2021 in Japan, we accidentally encountered a white-tailed sea eagle that had a fatal outcome due to natural infection with a GS/GD96-lineage H5N8 HPAI virus of clade 2.3.4.4b, allowing us to compare experimental and natural infections in the same rare raptor species. Our experiments demonstrated the susceptibility of white-tailed sea eagles to the GS/GD96-lineage H5 HPAI virus with efficient replication in systemic organs. The potential for the viruses to spread within the white-tailed sea eagle population through indirect transmission was also confirmed. Comprehensive comparisons of both viral distribution and histopathological observations between experimentally and naturally infected white-tailed sea eagles imply that viral replication in the brain is responsible for the disease severity and mortality in this species. These findings provide novel insights into the risk assessment of H5 HPAI viral infection in white-tailed sea eagles, proper diagnostic procedures, potential risks to artificially fed eagle populations and persons handling superficially healthy eagles, potential impact of intragastric infection on eagle outcomes, and possibility of severity of the disease being attributed to viral replication in the brain.